FOREIGN INVESTMENTS IN STRATEGIC INDUSTRIES, THEIR REGULATION AND CONSEQUENCES FOR THE ECONOMY (International journal of artificial intelligence, 2025)
This article examines the role of foreign investment in the development of strategic sectors of the national economy. It analyzes the system of government regulation aimed at ensuring economic security, protecting national interests, and increasing the efficiency of foreign capital use. Particular attention is paid to the legal aspects of admitting foreign investors to strategic sectors such as energy, transport, telecommunications, and mining. A comparative analysis of international experience demonstrates that a balanced investment policy contributes to accelerated technological progress, increased productivity, and the creation of new jobs. However, excessive dependence on foreign capital can lead to the loss of economic sovereignty and strategic resources, requiring careful regulation and transparency of investment processes.